Rasionalitas Konversi Bank Konvensional ke Bank Syariah - Aji Damanuri (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2012)
Shari’ah banking, for the last ten years, has increased in prosperity not only at the quantity of conventional banks but also at the count of assets and customers. This economical opportunity drives amount of conventional banks both to convert their institutions to be shari’ah banks and to open officially shari’ah platform units with their own assets. This system takes a significant question, is the conversion effected by both banker ideological factor and capitalists or pure economical rational calculation? Is a religious consideration linked to economical rationality? This paper is to elaborate the conversion using not only ”˜choice theory’ but also ”˜rational action’to seek religious action possibility in a reasonable way of shari’ah banking.